Insulin-Like Growth Factor 1: At the Crossroads of Brain Development and Aging - Wrigley, Sarah; Arafa, Donia; Tropea, Daniela (Frontiers in Cellular Neuroscience, 2017)
Insulin-like growth factor 1 (IGF1) is a polypeptide hormone structurally similar to insulin. It is central to the somatotropic axis, acting downstream of Growth Hormone. It activates both the MAP kinase and PI3K signalling pathways, acting in almost every tissue in the body to promote tissue growth and maturation through upregulation of anabolic processes. Overall GH and IGF1 signalling falls with age, suggesting that it is this reduced IGF1 activity that leads to age-related changes in organisms. However, mutations that reduce IGF1-signalling activity can dramatically extend the lifespan of organisms. Therefore, the role of IGF1 in the overall aging process is unclear. This review will focus on the role of IGF1 in brain development and aging. The evidence points towards a role for IGF1 in neurodevelopment both prenatally and in the early post-natal period, and in plasticity and remodelling throughout life. This review will then discuss the hallmarks of aging and cognitive decline associated with falls in IGF1 levels towards the end of life. Finally, the role of IGF1 will be discussed within the context of both neuropsychiatric disorders caused by impaired development of the nervous system, and neurodegenerative disorders associated with aging. IGF1 and its derivatives are shown to improve the symptoms of certain neuropsychiatric disorders caused by deranged neurodevelopment and these effects have been correlated with changes in the underlying biology in both in vitro and in vivo studies. On the other hand, studies looking at IGF1 in neurodegenerative diseases have been conflicting, supporting both a role for increased and decreased IGF1 signalling in the underlying pathogenesis of these diseases.